2018
DOI: 10.5546/aap.2018.eng.333
|View full text |Cite
|
Sign up to set email alerts
|

Post-extubation non-invasive ventilation in the pediatric intensive care unit: a multicenter study

Abstract: The use of post-extubation NIV may be a useful tool to prevent reintubation with invasive mechanical ventilation. Immunocompromised patients and those with neurological history had a higher rate of failure. Patients with failure tolerated less hours of NIV and had a longer length of stay in the pediatric intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Several models also predict HFNC failure such as RR above the 90th percentile for age at triage [1,27], no RR or HR change within sixty minutes [28] and worsening pediatric early warning scores [29]. The failure rate (13.4%) in this study was within the reported ranges of 3% and 30% [3,8,30]. Neither the treatment modality (NIPPV / HFNC) nor the therapy institution (first-line / rescue therapy) was associated with NIV failure.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Several models also predict HFNC failure such as RR above the 90th percentile for age at triage [1,27], no RR or HR change within sixty minutes [28] and worsening pediatric early warning scores [29]. The failure rate (13.4%) in this study was within the reported ranges of 3% and 30% [3,8,30]. Neither the treatment modality (NIPPV / HFNC) nor the therapy institution (first-line / rescue therapy) was associated with NIV failure.…”
Section: Discussionmentioning
confidence: 55%
“…Complex chronic conditions inevitably influence the ventilation strategies [8,19,33]. SCARF (Early CPAP in Acute Respiratory Failure) study is a recent, randomized, controlled study performed in children with a high-risk combination of impaired immunity and ARF [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weaning from mechanical ventilation (MV) can be defined as the gradual reduction in respiratory support, assigning a spontaneous breathing time to let the child take responsibility for an acceptable gas exchange [3]. The term extubation failure (EF) represents a set of conditions that determine the need for reintubation and MV restoration within the first 24-72h after the removal of the endotracheal tube [3,4]. Non-invasive mechanical ventilation (NIMV) offers an alternative to intubation with possibility of providing MV in the treatment of acute respiratory failure in infants and children [1] and helps restore diaphragm function as soon as possible in case of good patient-machine synchronization.…”
Section: Problem Statement and Analysis Of The Latest Researchmentioning
confidence: 99%